Exploring the functional features of melon peel flour for healthier bakery products - Silva, M.A. (2024)
The use of fruit by-products to develop new food products could be an advantageous approach to meet the demand for healthy foods and reduce food waste. In this study, the amino acid and mineral profiles of melon peel flour were evaluated. Non-essential/toxic elements were also determined. Furthermore, two formulations (biscuit and muffin) were developed with 50% and 100% melon peel flour, respectively. The bioaccessibility of essential minerals in these two formulations was also determined. These innovative products presented interesting contents of amino acids and high levels of minerals, contributing significantly to daily mineral requirements, mainly magnesium (18–23%), phosphorus (13–28%), molybdenum (14–17%), and manganese (10–13%). Regarding the in vitro bioaccessibility of minerals in the developed formulations, magnesium, manganese, sodium, and phosphorus were those with the highest values (75–108%). Based on these results, melon peel has the potential to improve global food security, nutrition, economic well-being, and overall health and well-being.